Incidence and long‐term outcomes of squamous cell bladder cancer after deceased donor renal transplantation. (11th October 2013) - Davis, N. F.; McLoughlin, L. C.; Dowling, C.; Power, R.; Mohan, P.; Hickey, D.; Smyth, G.; Eng, M.; Little, D. M.
Abstract Objective To review the incidence and long‐term outcomes of squamous cell carcinoma (SCC) of the bladder in patients after kidney transplantation. Methods Between January 1976 and March 2013, five patients from one center (0.0013%) developed SCC of the bladder after undergoing a deceased donor kidney transplant. Their relevant risk factors included long‐term self‐intermittent catheterization/indwelling catheter (n = 2), smoking history (n = 2), and a prior history of cyclophosphamide treatment for vasculitis (n = 1). Primary outcome variables were overall patient survival and latency period between transplantation and SCC diagnosis. Results The duration of long‐term follow‐up was 94 ± 89 (range: 4–239) months. The latency period between transplantation and bladder SCC was 87 ± 87 (range: 2–228) months, and all five patients were immunosuppressed with tacrolimus, mycophenolate mofetil, and prednisone. Four patients had suspected metastases upon presentation, and one patient presented with organ‐confined disease. This patient underwent a radical cystectomy and remains disease free eight months post‐operatively. Despite radical treatment, the remaining four patients died from metastatic disease 7 ± 4.4 (range: 2–11) months after their initial diagnosis. Conclusion SCC of the bladder has a poor prognosis particularly in renal transplant patients. Early detection with flexible cystourethroscopy in patients with risk factors for SCC may improve long‐term outcomes in this patient cohort.